LEGAL SOLUTION FOR LOCAL BUDGET CORRUPTION CRIME IN COVID-19 PANDEMIC ERA - Siti Nur Mutiyah; Mulyono Mulyono; Siti Nur Intihani (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2022)
The crime of corruption in the misuse of village funds in Indonesia has long been a public concern. Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, still seems to be ineffective in making perpetrators of misuse of village funds afraid and deterrent. One example of a criminal act of corruption in the Sukowarno village fund, Suka Karya District, Musi Rawas Regency, there are indications of irregularities in the accountability of the Village Fund for communities affected by the Covid-19 pandemic. Data analysis was carried out using qualitative data analysis methods. Based on the results of the study, the legal settlement of the criminal act of corruption in village funds during the covid-19 pandemic (study of the Palembang District Court Decision Number: 06/Pid.Sus-TPK/2021/PN.Plg) was appropriate and in terms of the application of material criminal law. the defendant's actions were legally and convincingly proven guilty of committing a criminal act of corruption as stated in the Primary Public Prosecutor's indictment in Article 2 of the Law on the Eradication of Criminal Acts of Corruption. The Panel of Judges sentenced the defendant to imprisonment for 8 (eight) years and a fine of Rp. 200,000,000.00 (two hundred million rupiah), this illustrates that the Panel of Judges is serious about enforcing the law against perpetrators of misuse of village funds, although a verdict is still expected. higher. However, according to the author, the Panel of Judges also carried out non-juridical considerations based on the background of the defendant, the consequences of the defendant's actions should the perpetrators of the Corruption Crime of Village Funds During the Covid-19 Pandemic be sentenced to death, the aim is to create a deterrent effect and prevent recurrence. the same thing in the future.